Sintesis antigen AFB1-BSA dan konjugasi antibodi anti AFB1-BSA dengan nanopartikel emas sebagai pereaksi imunostrip - Ita Krissanti; Agustin Indrawati; Romsyah Maryam (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2020)
Aflatoksin B1 (AFB1) often contaminates a great variety of foods and animal feeds that will be dangerous if con-sumed by humans or animals. Rapid detection techniques that can be used in the field is really needed to monitor AFB1 contamination. The aims of this study were to perform synthesis of AFB1-BSA antigen and conjugation of antibody against AFB1-BSA to gold nanoparticle as immunostrip-test reagents. The AFB1-CMO was identified on TLC and AFB1-BSA was characterized using SDS PAGE. The AFB1-CMO formation indicated as a blue spot at 0.45 retention factor (Rf) on TLC and the AFB1-BSA antigen revealed as a single band protein at about 72 kDa molecular weight on the SDS PAGE. Conjugation of antibody against AFB1-BSA to gold nanoparticle resulted in the formation of red-dish purple compound which can be used for the detection of AFB1 on immunostrip. The optimum composition achieved in concentration of AFB1-BSA 1-1.5 mg/ml, IgG anti rabbit 0.1 mg/ml, and antibody against AFB1-BSA-gold nanoparticle conjugate in 0.5x0.5 cm² area characterized by the establishment of two reddish purple lines in the test and control zone.